2014
DOI: 10.1002/adfm.201400935
|View full text |Cite
|
Sign up to set email alerts
|

A Lithium‐Sulfur Battery with a High Areal Energy Density

Abstract: 5359 www.MaterialsViews.com wileyonlinelibrary.com density, which is approximately 6.6 times larger than that of the current intercalationbased LIBs (≈387 Wh kg −1 ). [5][6][7][8] Remarkably, recent research efforts have been successful in resolving the chronic technical challenges associated with sulfur electrodes, especially dissolution of lithium polysulfi des and low electric conductivity of elemental sulfur. [9][10][11][12] The representative solutions along this direction include sulfur-carbon composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
172
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 47 publications
4
172
0
Order By: Relevance
“…Recently Kim et al demonstrated a Li-S cell with an electrode loading of 9 mAh/cm 2 , evidencing that engineered sulfur cathodes could achieve and preserve the required high areal capacities by tailoring both the anode and the cathode. 23 We conclude that the limiting factor in achieving the Li-S cathode targets is the need to identify electrolyte systems and strategies that enable starved electrolyte based electrodes that also achieve good cyclability and rate capability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Kim et al demonstrated a Li-S cell with an electrode loading of 9 mAh/cm 2 , evidencing that engineered sulfur cathodes could achieve and preserve the required high areal capacities by tailoring both the anode and the cathode. 23 We conclude that the limiting factor in achieving the Li-S cathode targets is the need to identify electrolyte systems and strategies that enable starved electrolyte based electrodes that also achieve good cyclability and rate capability.…”
Section: Resultsmentioning
confidence: 99%
“…8 A variety of porous carbons, polymers, metal oxides and functionalized graphenes have been developed in an attempt to contain the soluble polysulfide intermediates through both physical and chemical interactions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In addition to mitigating the polysulfide shuttle, engineered S cathodes have enhanced electronic conductivity and may accommodate the volume change in the cathode during cycling. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Other approaches have focused on designing new electrolytes with limited polysulfide solubility thereby suppressing the polysulfide shuttle leading to excellent coulombic efficiency and improved capacity retention.…”
Section: 2mentioning
confidence: 99%
“…That the resistance increases similarly rapidly for both cells is further evidence that electrolyte consumption is responsible for cell failure, with said consumption occurring faster if the negative electrode excess is lower, with an increasingly unfavourable morphology of the lithium electrode the likely cause. 19 Simple strategies which target improved morphology of lithium, for example heavier alkali metal additives, 20 may be particularly effective in this regard.…”
Section: 18mentioning
confidence: 99%
“…Reports show that areal capacities for anode materials that have high gravimetric capacities, e.g., double walled Si-nanotube is approximately seventeen times less than the areal capacity for a graphite anode (4.1 mAh/cm 2 ) [58]. It is equivalent to material loading of 0.1 mg/cm 2 .…”
Section: Light Weightmentioning
confidence: 99%